Community Pharmacist-Provided Wellness and Monitoring Services in an Employee Wellness Program: A Four-Year Summary - Yifei Liu; Kendall D. Guthrie; Justin R. May; Kristen L. DiDonato (MDPI AG, 2019)
Objective: To assess the clinical outcomes of participants of an employee wellness program during four years of service implementation. Methods: A prospective cohort study was conducted at 15 independent community pharmacy chain locations in northwest and central Missouri. A total of 200 participants were enrolled in an employee wellness program, and the program included five monitoring groups—cholesterol, blood pressure, blood glucose, weight, and healthy participant groups. Participants selected a pharmacist wellness coordinator and wellness appointments were conducted, consisting of education, goal-setting, and monitoring through physical assessment and point of care testing. The primary outcome measures were total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (FBG), body mass index (BMI), and waist circumference (WC). The secondary outcome measures were the proportion of patients who achieved the clinical value goals at baseline versus 48 months. The primary outcome measures among data collection time points were compared using one-way analysis of variance (ANOVA) tests, and the secondary outcomes were compared between baseline and 48 months by Chi-square or Fisher’s exact tests. One-way ANOVA post hoc tests were also performed using least significant difference, to further identify which time points differed from each other. Results: At baseline, there were 134 patients in the cholesterol monitoring group, 129 in the weight monitoring group, 117 in the blood pressure monitoring group, 46 in the blood glucose monitoring group, and 26 in the healthy participant monitoring group. For patients in the blood pressure monitoring group, compared with baseline, there was a significant decrease in DBP at months 12, 24, 36, and 48, and a significant increase in the proportion of patients achieving blood pressure goals at 48 months. For patients in the blood glucose monitoring group, compared with baseline, there was a significant decrease in FBG at months 12, 24, 36, and 48, and a significant increase in the proportion of patients achieving blood glucose goals at 48 months. Conclusions: Pharmacist-led wellness visits provided to employee wellness patients in a community pharmacy may lead to improvements in BP and FBG values.